2016
DOI: 10.1038/srep30668
|View full text |Cite
|
Sign up to set email alerts
|

Structural basis for misregulation of kinesin KIF21A autoinhibition by CFEOM1 disease mutations

Abstract: Tight regulation of kinesin activity is crucial and malfunction is linked to neurological diseases. Point mutations in the KIF21A gene cause congenital fibrosis of the extraocular muscles type 1 (CFEOM1) by disrupting the autoinhibitory interaction between the motor domain and a regulatory region in the stalk. However, the molecular mechanism underlying the misregulation of KIF21A activity in CFEOM1 is not understood. Here, we show that the KIF21A regulatory domain containing all disease-associated substitutio… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
43
1

Year Published

2017
2017
2024
2024

Publication Types

Select...
6
1

Relationship

2
5

Authors

Journals

citations
Cited by 32 publications
(46 citation statements)
references
References 63 publications
(102 reference statements)
2
43
1
Order By: Relevance
“…To assess the oligomerization state of KIF21B rCC, we performed sedimentation velocity experiments (Figure 6—figure supplement 4B), which revealed a molecular weight of 11 kDa for the polypeptide chain fragment (calculated molecular weight of KIF21B rCC: 9.5 kDa). These biophysical results are consistent with KIF21B rCC forming an intramolecular antiparallel coiled coil in solution, very similar to the one we described for KIF21A (Bianchi et al, 2016). …”
Section: Resultssupporting
confidence: 91%
See 3 more Smart Citations
“…To assess the oligomerization state of KIF21B rCC, we performed sedimentation velocity experiments (Figure 6—figure supplement 4B), which revealed a molecular weight of 11 kDa for the polypeptide chain fragment (calculated molecular weight of KIF21B rCC: 9.5 kDa). These biophysical results are consistent with KIF21B rCC forming an intramolecular antiparallel coiled coil in solution, very similar to the one we described for KIF21A (Bianchi et al, 2016). …”
Section: Resultssupporting
confidence: 91%
“…The potent effect of KIF21B on MT plus-end polymerization is due to the presence of two MT-binding regions in its tail, which help to prevent kinesin dissociation from the tip of the growing MT. We also found that the region responsible for autoinhibition in KIF21A (Bianchi et al, 2016) is conserved in KIF21B. However, instead of blocking the motor, this element reduced motor detachment from growing MT plus ends and thus contributed to MT pause induction.…”
Section: Introductionmentioning
confidence: 63%
See 2 more Smart Citations
“…These genes have interesting functionality. For example, HNRNPDL and RBM39 function in transcription regulation [59,60], HNRNPDL and SRSF2 regulate alternative splicing [59,61], MPRIP is involved in stress granule formation [62], CHID1 has a role in pathogen sensing [63], and KIF21A has been implicated in neurological diseases [64]. Consistent with the selection criterion, RT-PCR validation of AS events showed significant missplicing in ZIKV PR -infected cells with the greatest difference in PSI values between Mock and ZIKV PR was ~28% (RBM39).…”
Section: Exon Skipping Is a Major Splicing Event During Zikv Pr Zikmentioning
confidence: 82%